A MOF-derived Co 1-x Use of S / MoS2 composite in sodium-ion batteries

CN122931002APending Publication Date: 2026-10-16HENAN INST OF SCI & TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202610777515.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-06-01
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

[0005]本发明提供一种MOF衍生的Co1-xS/MoS2复合材料及其在钠离子电池中的应用,旨在解决高容量和高电导率不可兼得的问题,实现比容量、倍率、循环等综合性能的提升,且工艺简单、成本较低,适合产业化

Benefits of technology

[0019] This invention uses zeolite imidazole ester framework materials (ZIFs) to derive and prepare Co 1-x In the S/MoS2 composite material, on the one hand, the ZIFs-derived carbon matrix enables in-situ N doping, effectively improving the electronic conductivity of the composite material; on the other hand, Co... 1-x The uniform embedding of S/MoS2 nanoparticles within the nanoporous carbon matrix effectively inhibits the aggregation of active materials and solves the volume expansion problem of the electrode material during charge and discharge. Co in the composite material... 1-x S and MoS2 are tightly bound at the nanoscale, with MoS2 providing a stable layered framework, and Co... 1-x S provides high electrical conductivity, and the two form a tightly coupled heterogeneous interface that achieves synergy between capacitive behavior and diffusion control. This significantly reduces charge transfer resistance and the migration barrier of sodium ions at the interface, thereby achieving efficient sodium storage. As a result, this composite material exhibits excellent specific capacity, rate performance and outstanding cycle performance when used in sodium-ion batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122931002A_ABST
    Figure CN122931002A_ABST
Patent Text Reader

Abstract

The application belongs to the technical field of sodium ion battery materials, and particularly relates to a MOF derived Co 1‑x S / MoS2 composite material and application thereof in sodium ion batteries. The composite material contains Co 1‑x S and MoS2 nanocrystals and nitrogen-doped carbon, wherein Co 1‑x S / MoS2 nanoparticles are uniformly embedded in a nanoporous carbon matrix, effectively inhibiting the agglomeration of active substances and solving the volume expansion problem of electrode materials during the charging and discharging process; the carbon matrix derived from ZIFs realizes in-situ N doping, effectively improving the electronic conductivity of the composite material; Co 1‑x S and MoS2 nanoscale coupling form a heterostructure, significantly reducing the charge transfer resistance and the migration energy barrier of sodium ions at the interface, thereby realizing efficient sodium storage, so that the composite material exhibits excellent specific capacity, rate performance and outstanding cycle performance when used as a negative electrode material of a sodium ion battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of sodium-ion battery materials technology, specifically relating to a MOF-derived Co 1-x S / MoS2 composite materials and their application in sodium-ion batteries. Background Technology

[0002] Due to the increasingly severe energy crisis and the growing environmental pollution, the world is undergoing a profound energy transition aimed at reducing dependence on fossil fuels. Developing efficient and sustainable energy storage systems has become a core issue in global technological development. The rapid development of renewable energy sources such as solar and wind power has placed higher demands on electrochemical energy storage technologies to address their inherent geographical and fluctuating challenges. Against this backdrop, sodium-ion batteries (SIBs), as a highly promising electrochemical energy storage technology, are receiving widespread attention from global research and industry. Sodium resources are abundant in the Earth's crust and can be extracted from seawater, offering significant cost advantages and resource autonomy. Furthermore, sodium's redox potential is close to that of lithium, and sodium and lithium are adjacent elements in the periodic table with similar physicochemical properties, demonstrating enormous application potential in the field of electrochemical energy storage. Sodium-ion batteries are expected to play a crucial role in smart grids, electric transportation, and stationary energy storage, providing a solid guarantee for building a safe, economical, and sustainable energy system.

[0003] In sodium-ion battery systems, the performance of the anode material directly affects the overall energy density, cycle life, and rate performance of the battery. Currently, anode materials can be mainly classified into three categories: intercalation-type (such as graphite and hard carbon), alloy-type (such as Si, Sn, and Sb), and conversion-type (such as transition metal oxides, sulfides, and selenides). Among conversion-type anode materials, transition metal sulfides (TMSs) have been extensively studied due to their high theoretical capacity and multi-electron transfer characteristics. Cobalt sulfide (Co...) is a particularly important example. 1-x Molybdenum disulfide (MoS2) and sodium sulfide (S) are two representative materials. However, single-component metal sulfide electrodes have some problems, including slow electron / ion migration, poor conductivity, and Na+. + The scarcity of storage sites leads to low battery capacity and poor rate performance. 1-x Sodium (S) typically exhibits superior electronic conductivity compared to MoS2, which is crucial for rapid charge transport, but its volume changes more drastically. MoS2 has a typical layered structure with an interlayer spacing of approximately 0.62 nm, providing relatively open insertion channels for larger sodium ions. However, MoS2 has low intrinsic electronic conductivity, classifying it as a semiconductor material, which limits its performance at high rates.

[0004] To address the aforementioned issues, patent CN109192974A provides a method for preparing a cobalt sulfide / molybdenum disulfide core-shell structured anode material. First, pure-phase cobalt sulfide (Co) is prepared via a hydrothermal reaction. 1-x S), then it is mixed with a certain amount of sodium molybdate, thiourea and glucose solution, and then the molybdenum disulfide is uniformly coated on the surface of cobalt sulfide by hydrothermal reaction to obtain core-shell structured cobalt sulfide (Co). 1-x MoS2@CoS2@porous carbon fiber composite material. This material exhibits high specific capacity and stable cycle performance in lithium-ion batteries, but performs poorly in sodium-ion batteries. Patent CN117790706A provides a MoS2@CoS2@porous carbon fiber composite material, its preparation method, and its application. In this method, cobalt acetate tetrahydrate is added as a cobalt source during the preparation of the electrospinning solution. Then, through electrospinning and sealing vulcanization steps, cobalt disulfide particles are uniformly embedded in carbon nanofibers to modify the carbon nanofibers. Finally, molybdenum disulfide is uniformly grown on the carbon nanofibers using a hydrothermal method to obtain the MoS2@CoS2@porous carbon fiber composite material. This method requires high-end equipment for electrospinning, is technically complex and costly, and has poor prospects for industrialization. Summary of the Invention

[0005] This invention provides a MOF-derived Co 1-x The S / MoS2 composite material and its application in sodium-ion batteries aim to solve the problem of the trade-off between high capacity and high conductivity, and to improve the comprehensive performance of specific capacity, rate capability, and cycle life. Moreover, the process is simple and the cost is low, making it suitable for industrialization.

[0006] To achieve the above objectives, the present invention first provides a MOF-derived Co 1-x S / MoS2 composite material containing Co 1-x S and MoS2 nanocrystals, Co 1-x The nanoscale coupling of S and MoS2 forms a heterostructure that can be used as a negative electrode material for sodium-ion batteries.

[0007] Preferably, the molar ratio of Co to Mo in the composite material is 1-5:1, more preferably 2.5-3.0:1.

[0008] Those skilled in the art will understand that heterostructures, by tightly binding two or more different components of materials at the nanoscale, generate unique physicochemical effects at the interface. Due to the difference in Fermi levels between the two components, a built-in electric field is spontaneously formed at the heterostructure interface, which can effectively accelerate charge separation and transport, reduce charge transfer resistance, and induce sodium ion enrichment at the interface and reduce its migration energy barrier. This significantly enhances electrochemical reaction kinetics, optimizes the sodium storage specific capacity and rate performance of the electrode material, and achieves synergistic effects with half the effort.

[0009] Furthermore, the composite material also contains nitrogen-doped carbon, possessing a nanoporous structure, with a carbon content of 10-50% wt% of the composite material's mass. Its nanoporous structure can accommodate Co. 1-x S / MoS2 microcrystals effectively alleviate the volume expansion of electrode materials during charging and discharging, and also help suppress the aggregation of active materials. Nitrogen doping in carbon further improves the electronic conductivity of the composite material.

[0010] Secondly, this invention provides a method for preparing the above-mentioned composite material, the method comprising synthesizing the precursor ZIF-CoMo and synthesizing Co 1-x S / MoS2 composite material.

[0011] Further, the synthetic precursor ZIF-CoMo is prepared by adding a dispersant, molybdic acid, 2-methylimidazole, and cobalt acetate tetrahydrate to a DMF solvent, stirring to obtain a mixture, reacting at 150-170 °C for 10-20 h, filtering, washing, and drying to obtain a blue powdered precursor ZIF-CoMo.

[0012] Preferably, the dispersant is polyvinylpyrrolidone, and the amount used is 0.5-5%wt of the solvent. The mass ratio of 2-methylimidazole to cobalt acetate tetrahydrate is 0.5-2:1, the molar ratio of molybdic acid to cobalt acetate tetrahydrate is 0.1-1:1, and the ratio of the total mass of each solid raw material to the mass of DMF solvent is 5-20:100.

[0013] In some embodiments, the washing is performed by centrifugation with methanol three times, and the drying is performed by heating at 60°C for 1-3 hours.

[0014] Furthermore, the synthesized Co 1-x The S / MoS2 composite material is obtained by carbonizing the precursor ZIF-CoMo at high temperature under an inert atmosphere to obtain an intermediate product, followed by high-temperature vulcanization under an inert atmosphere to obtain Co. 1-x S / MoS2 composite material.

[0015] Preferably, the high-temperature carbonization temperature is 600-800℃ and the time is 2-3h, and the high-temperature sulfidation is to react the intermediate product with sulfur vapor at 700-900℃ for 1-3h.

[0016] Furthermore, this invention provides the application of the aforementioned composite material in sodium-ion batteries. Using this composite material as the negative electrode material of a sodium-ion battery, and matching it with a binder and conductive agent to form the negative electrode, and then matching it with a positive electrode and electrolyte, a sodium-ion battery is obtained. The battery exhibits excellent cycle performance and outstanding rate performance. The active material of the positive electrode has no special requirements and can be common sodium-ion battery positive electrode materials in the prior art, such as layered transition metal oxides, Prussian white, manganese-based / copper-based Prussian blue, polyanionic compounds, etc.

[0017] The composite material of the present invention can also be used to make a button cell using sodium metal as the counter electrode.

[0018] Compared with the prior art, the present invention has the following beneficial effects:

[0019] This invention uses zeolite imidazole ester framework materials (ZIFs) to derive and prepare Co 1-x In the S / MoS2 composite material, on the one hand, the ZIFs-derived carbon matrix enables in-situ N doping, effectively improving the electronic conductivity of the composite material; on the other hand, Co... 1-x The uniform embedding of S / MoS2 nanoparticles within the nanoporous carbon matrix effectively inhibits the aggregation of active materials and solves the volume expansion problem of the electrode material during charge and discharge. Co in the composite material... 1-x S and MoS2 are tightly bound at the nanoscale, with MoS2 providing a stable layered framework, and Co... 1-x S provides high electrical conductivity, and the two form a tightly coupled heterogeneous interface that achieves synergy between capacitive behavior and diffusion control. This significantly reduces charge transfer resistance and the migration barrier of sodium ions at the interface, thereby achieving efficient sodium storage. As a result, this composite material exhibits excellent specific capacity, rate performance and outstanding cycle performance when used in sodium-ion batteries. Attached Figure Description

[0020] Figure 1 XRD and Co of the composite materials obtained in Examples 1-3 1-x A comparison chart of standard PDFs for S and MoS2.

[0021] Figure 2 The images shown are TEM images, SAED images, and EDS images of the composite material obtained in Example 1.

[0022] Figure 3 The image shows the XRD pattern of the composite material obtained in Comparative Example 4. Detailed Implementation

[0023] The technical solution of the present invention will be further described in detail below with reference to specific embodiments. These embodiments are only for illustrating the present invention and should not be regarded as limiting the scope of the present invention or the method of implementing the present invention. All other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0024] Example 1

[0025] Preparation of MOF-derived Co 1-x S / MoS2 composite material.

[0026] S1. Synthesis of the precursor ZIF-CoMo. First, 120 mL of N,N-dimethylformamide (DMF) and 0.9 g of polyvinylpyrrolidone (PVP) were added to a three-necked flask. Then, 0.64 g of molybdic acid (H₂MoO₄), 3.95 g of 2-methylimidazolium (2-Mim), and 4.98 g of cobalt acetate tetrahydrate (C₄H₆CoO₄·4H₂O) were added, with a molar ratio of molybdic acid to cobalt acetate tetrahydrate of 1:5. The mixture was then refluxed and stirred at 160 °C for 12 h, filtered, washed three times with anhydrous methanol by centrifugation, and dried at 60 °C for 2 h to obtain 3.1 g of blue powdered precursor ZIF-CoMo.

[0027] S2, synthesizing Co 1-x S / MoS2 composite material. The precursor obtained from S1 was placed in a tube furnace and held at 700℃ for 2 h under Ar flowing atmosphere protection to obtain 1.3 g of carbonization intermediate. Then, the intermediate and 5.2 g of sublimed sulfur powder were placed on both sides of a small ceramic boat and placed in a tube furnace. The furnace was held at 700℃ for 2 h under Ar flowing atmosphere protection, and then cooled to room temperature to obtain Co. 1-x 1.85g of S / MoS2 composite material.

[0028] Example 2

[0029] Preparation of MOF-derived Co 1-x S / MoS2 composite material.

[0030] S1. Synthesis of the precursor ZIF-CoMo. First, 120 mL of N,N-dimethylformamide (DMF) and 0.9 g of polyvinylpyrrolidone (PVP) were added to a three-necked flask. Then, 1.92 g of molybdic acid (H₂MoO₄), 3.95 g of 2-methylimidazolium (2-Mim), and 4.98 g of cobalt acetate tetrahydrate (C₄H₆CoO₄·4H₂O) were added, with a molar ratio of molybdic acid to cobalt acetate tetrahydrate of 3:5. The mixture was then refluxed and stirred at 160 °C for 12 h, filtered, washed three times with anhydrous methanol by centrifugation, and dried at 60 °C for 2 h to obtain 5.0 g of powdered precursor ZIF-CoMo.

[0031] S2, synthesizing Co 1-x S / MoS2 composite material. The precursor obtained from S1 was placed in a tube furnace and held at 700℃ for 2 h under Ar flowing atmosphere protection to obtain 2.6 g of carbonization intermediate. Then, the intermediate and 10.4 g of sublimed sulfur powder were placed on both sides of a small ceramic boat and placed in a tube furnace. The furnace was held at 700℃ for 2 h under Ar flowing atmosphere protection, and then cooled to room temperature to obtain Co. 1-x 3.7g of S / MoS2 composite material.

[0032] Example 3

[0033] Preparation of MOF-derived Co 1-x S / MoS2 composite material.

[0034] S1. Synthesis of the precursor ZIF-CoMo. First, 120 mL of N,N-dimethylformamide (DMF) and 0.9 g of polyvinylpyrrolidone (PVP) were added to a three-necked flask. Then, 0.51 g of molybdic acid (H₂MoO₄), 3.95 g of 2-methylimidazolium (2-Mim), and 4.98 g of cobalt acetate tetrahydrate (C₄H₆CoO₄·4H₂O) were added, with a molar ratio of molybdic acid to cobalt acetate tetrahydrate of 0.8:5. The mixture was then refluxed and stirred at 160 °C for 12 h, filtered, washed three times with anhydrous methanol by centrifugation, and dried at 60 °C for 2 h to obtain 3.4 g of powdered precursor ZIF-CoMo.

[0035] S2, synthesizing Co 1-x S / MoS2 composite material. The precursor obtained from S1 was placed in a tube furnace and held at 700℃ for 2 h under Ar flowing atmosphere protection to obtain 1.6 g of carbonization intermediate. Then, the intermediate and 6.4 g of sublimed sulfur powder were placed on both sides of a small ceramic boat and placed in a tube furnace. The furnace was then held at 700℃ for 2 h under Ar flowing atmosphere protection, and cooled to room temperature to obtain Co. 1-x 2.1g of S / MoS2 composite material.

[0036] Example 4

[0037] Preparation of MOF-derived Co 1-x S / MoS2 composite material.

[0038] The only difference from Example 1 is that the vulcanization temperature in step S2 is 800°C, while the other parameters, steps, and amounts are completely the same.

[0039] Example 5

[0040] Preparation of MOF-derived Co 1-x S / MoS2 composite material.

[0041] The only difference from Example 1 is that the vulcanization temperature in step S2 is 900°C, while the other parameters, steps, and amounts are completely the same.

[0042] Comparative Example 1

[0043] Preparation of MOF-derived Co 1-x S composite material.

[0044] The only difference from Example 1 is that molybdic acid is not added in step S1; all other parameters, steps, and amounts are exactly the same.

[0045] Comparative Example 2

[0046] Prepare MOF-derived MoS2 composite materials.

[0047] The only difference from Example 1 is that cobalt acetate tetrahydrate is not added in step S1; all other parameters, steps, and amounts are exactly the same.

[0048] Comparative Example 3

[0049] The Co obtained from Comparative Example 1 1-x The S composite material and the MoS2 composite material obtained in Comparative Example 2 were blended at a mass ratio of 2.41:1.

[0050] Example 4

[0051] Prepare MOF-derived composite materials.

[0052] The only difference from Example 1 is that the vulcanization temperature in step S2 is 600°C, while the other parameters, steps, and amounts are completely the same.

[0053] Composite material characterization

[0054] The following tests were performed on the composite materials obtained in the examples and comparisons:

[0055] XRD patterns were acquired using a Bruker D8 Advance X-ray diffractometer for phase analysis.

[0056] Microstructure was observed using a FEI-Tecnai G2 F30 high-resolution transmission electron microscope (USA).

[0057] The elemental contents of cobalt and molybdenum were determined using an Agilent 5800 inductively coupled plasma optical emission spectrometer (ICP-OES).

[0058] Carbon content was determined using a German Netzsch TG209 F3 thermogravimetric analyzer (TGA).

[0059] Electrochemical testing

[0060] The electrode sheet used was prepared by mixing the composite material (active material), conductive agent (SuperP), and binder (PVDF) obtained in the above examples and comparative examples at a mass ratio of 6:2:2. Then, using NMP as a dispersant, the mixture was stirred evenly and coated onto copper foil. After standing for 40 min, it was placed in a vacuum drying oven at 80 ℃ for 12 h. Finally, the dried electrode sheet was cut into 14 mm diameter plates using a slicing machine for later use. Electrochemical performance tests were conducted on sodium-ion half-cells assembled using a CR2032 battery case. The prepared electrode sheet was used as the working electrode, a sodium metal sheet as the counter electrode, a glass fiber membrane as the separator, and 1 M NaClO4 + EC / PC + 5% FEC as the electrolyte. Constant current charge-discharge tests were performed on a NEWARE battery testing system, with a voltage range of 0.005-3V.

[0061] The test results are summarized in the table below.

[0062] Molar ratio Co:Mo Carbon content (%) Initial specific capacity (mAh) @ 0.05A / g Specific capacity (mAh) @ 3.2A / g Specific capacity (mAh) after 100 cycles @ 0.1A / g Example 1 2.69:1 33.02 515 378 456 Example 2 0.99:1 26.10 626 42 129 Example 3 3.6:1 34.26 489 113 189 Example 4 2.66:1 32.97 501 363 215 Example 5 2.71:1 33.53 480 344 140 Comparative Example 1 / 40.84 378 149 155 Comparative Example 2 / 13.05 845 24 51 Comparative Example 3 2.69:1 33.01 512 112 125

[0063] As can be seen from the data in the table, the Co / Mo molar ratio of the composite materials obtained in Examples 2, 1, and 3 gradually increased, but the rate performance and cycle performance did not gradually improve or decrease. Instead, an inflection point (reaching the optimal value) appeared at 2.69:1, indicating that a moderate excess of Co... 1-x The S phase can form a tightly coupled heterogeneous interface with the MoS2 phase, improving electrical conductivity. In Examples 1, 4, and 5, the rate performance and cycling performance gradually decrease with increasing vulcanization temperature, indicating that 700℃ is the optimal temperature. The rate performance and cycling performance of the single-metal composites or bimetallic composites obtained in Comparative Examples 1, 2, and 3 are significantly worse than those in Example 1, further confirming the effectiveness of Co in Example 1. 1-x The S phase and the MoS2 phase form a high-quality heterogeneous interface, resulting in a synergistic effect of capacitive behavior and diffusion control.

[0064] Characterization diagram of the composite material obtained in Example 1 ( Figure 2 In Figure (b), lattice fringes with a spacing of 0.25 nm and hexagonal Co phase are shown. 1-x The spacing between the (101) crystal planes of S is consistent with that of MoS2. Meanwhile, lattice fringes with a spacing of approximately 0.61 nm can be observed around the perimeter, corresponding to the (002) crystal planes of MoS2. This close lattice contact confirms the presence of Co. 1−x A clear heterogeneous interface is formed between S and MoS2. Figure (c) shows an HRTEM image of the material's edge region, where no obvious lattice fringes were observed, confirming the presence of amorphous carbon, which is N-doped carbon derived in situ from the organic ligands in the precursor ZIF-CoMo after high-temperature carbonization. Selected area electron diffraction (SAED) in Figure (d) further confirms the polycrystalline nature of the composite material. The diffraction rings correspond to Co... 1-x The (110) crystal plane of S and the (200) and (006) crystal planes of MoS2 further confirm the presence of Co. 1−x The S / MoS2 heterostructure was successfully constructed. EDS diagram (e) shows that the five elements Co, Mo, S, C, and N are uniformly distributed within the selected region. The distribution regions of Co and Mo highly overlap, indicating that Co... 1-x S and MoS2 achieved uniform recombination at the microscale, rather than forming independent phases. The distribution areas of S completely overlapped with those of Co and Mo, further confirming the successful formation of metal sulfides.

[0065] XRD pattern of the composite material obtained in Comparative Example 4 ( Figure 3The observation of CoS2 at 27.8°, 32.3°, 36.2°, 39.8°, and 46.3° corresponding to the (111), (200), (210), (211), and (220) crystal planes proves that the product obtained by sulfidation at 600°C is CoS2, not Co. 1−x S. Combining Comparative Example 4 with Examples 1, 4, and 5, the vulcanization temperatures are 600℃, 700℃, 800℃, and 900℃ respectively. The target product cannot be obtained at 600℃, the performance deteriorates at 800℃ and 900℃, and 700℃ is the optimal temperature. In other words, an inflection point occurs at 700℃, which is unpredictable.

Claims

1. A MOF-derived Co 1-x The application of S / MoS2 composite material in sodium-ion batteries is characterized by, The composite material contains Co. 1-x S and MoS2 nanocrystals, Co 1-x The nanoscale coupling of S and MoS2 forms a heterostructure that can be used as a negative electrode material for sodium-ion batteries.

2. The application according to claim 1, characterized in that, The molar ratio of Co to Mo in the composite material is 1-5:

1.

3. The application according to claim 1, characterized in that, The composite material also contains nitrogen-doped carbon and has a nanoporous structure.

4. The application according to claim 3, characterized in that, The carbon content of the composite material is 10-50%wt.

5. The application according to claim 1, characterized in that, The preparation method of the composite material includes synthesizing the precursor ZIF-CoMo and synthesizing Co. 1-x S / MoS2 composite material.

6. The application according to claim 5, characterized in that, The synthetic precursor ZIF-CoMo is prepared by adding a dispersant, molybdic acid, 2-methylimidazole, and cobalt acetate tetrahydrate to a DMF solvent, stirring to obtain a mixture, reacting at 150-170 °C for 10-20 h, and then filtering, washing, and drying to obtain a blue powder ZIF-CoMo.

7. The application according to claim 6, characterized in that, The dispersant is polyvinylpyrrolidone, used at 0.5-5% wt of the solvent amount; the mass ratio of 2-methylimidazole to cobalt acetate tetrahydrate is 0.5-2:1; the molar ratio of molybdic acid to cobalt acetate tetrahydrate is 0.1-1:1; and the ratio of the total mass of each solid raw material to the mass of DMF solvent is 5-20:

100.

8. The application according to claim 6, characterized in that, The washing process involves three centrifugal washes with methanol, and the drying process involves heating at 60°C for 1-3 hours.

9. The application according to claim 5, characterized in that, The synthetic Co 1-x The S / MoS2 composite material is obtained by carbonizing the precursor ZIF-CoMo at high temperature under an inert atmosphere to obtain an intermediate product, followed by high-temperature vulcanization under an inert atmosphere to obtain Co. 1-x S / MoS2 composite material.

10. The application according to claim 9, characterized in that, The high-temperature carbonization temperature is 600-800℃ and the time is 2-3h. The high-temperature sulfidation is to react the intermediate product with sulfur vapor at 700-900℃ for 1-3h.

Citation Information

Patent Citations

  • Cobalt sulfide / molybdenum disulfide core-shell structure lithium battery negative electrode material preparation method

    CN109192974A

  • MoS < 2 >-CoS < 2 >-porous carbon fiber composite material as well as preparation method and application thereof

    CN117790706A